(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Liquid media make up the largest part of the body, their movement ensures metabolism and oxygen supply to cells, therefore, mechanical and rheological properties, the flow of liquids are of particular interest to physicians and biologists. The article discusses methods for determining the viscosity and surface tension of saliva.